Bile Acid-Mediated Sphingosine-1-Phosphate Receptor 2 Signaling Promotes Neuroinflammation during Hepatic Encephalopathy in Mice - McMillin, Matthew; Frampton, Gabriel; Grant, Stephanie; Khan, Shamyal; Diocares, Juan; Petrescu, Anca; Wyatt, Amy; Kain, Jessica; Jefferson, Brandi; DeMorrow, Sharon (Frontiers in Cellular Neuroscience, 2017)
Hepatic encephalopathy (HE) is a neuropsychiatric complication that occurs due to deteriorating hepatic function and this syndrome influences patient quality of life, clinical management strategies and survival. During acute liver failure, circulating bile acids increase due to a disruption of the enterohepatic circulation. We previously identified that bile acid-mediated signaling occurs in the brain during HE and contributes to cognitive impairment. However, the influences of bile acids and their downstream signaling pathways on HE-induced neuroinflammation have not been assessed. Conjugated bile acids, such as taurocholic acid (TCA), can activate sphingosine-1-phosphate receptor 2 (S1PR2), which has been shown to promote immune cell infiltration and inflammation in other models. The current study aimed to assess the role of bile-acid mediated S1PR2 signaling in neuroinflammation and disease progression during AOM-induced HE in mice. Our findings demonstrate a temporal increase of bile acids in the cortex during azoxymethane (AOM)-induced HE and identified that cortical bile acids were elevated as an early event in this model. In order to classify the specific bile acids that were elevated during HE, a metabolic screen was performed and this assay identified that TCA was increased in the serum and cortex during AOM-induced HE. To reduce bile acid concentrations in the brain, mice were fed a diet supplemented with cholestyramine, which alleviated neuroinflammation by reducing proinflammatory cytokine expression in the cortex compared to the control diet-fed AOM-treated mice. S1PR2 was expressed primarily in neurons and TCA treatment increased chemokine ligand 2 mRNA expression in these cells. The infusion of JTE-013, a S1PR2 antagonist, into the lateral ventricle prior to AOM injection protected against neurological decline and reduced neuroinflammation compared to DMSO-infused AOM-treated mice. Together, this identifies that reducing bile acid levels or S1PR2 signaling are potential therapeutic strategies for the management of HE.